Policy and legal approaches relating to climate-friendly technologies - Mustafa, Maizatun (2018)
While Malaysia is putting efforts to limit greenhouse gases (GHG) emissions, its policy framework on the other hand is still focusing on fossil fuels and carbon-intensive activities as key drivers to growth. Economic development which is fuelled by oil, coal and natural gases can inevitably cause increased emissions and this in turn can pose a serious obstacle towards attaining climate objectives. In today’s expanding economies, policy makers must comprehend that resolutions undertaken to deal with climate change challenges need to be based on profound and transformational measures. Strengthening the level of ambition in terms of emission reduction should thus take into account trends in new technologies which are reshaping the present economies. Experiences elsewhere have indicated that emerging technologies which support low-carbon and climate resilient development can help towards attaining the climate change target. Such technologies, which can be applicable across a range of systems should therefore be considered by policy makers to be parts of the overall climate change initiatives. This presentation provides a review of existing Malaysia’s policy to reduce GHG emissions as well as the role of law to support technological change for tackling climate change. This presentation argues that policy objectives which contain opportunities for new technology and innovation can help nation to increase its option and to diversify its pathways in responding to climate change commitments.